CAN GOOD GOVERNANCE IN MOSQUES INCREASE THE PROSPERITY OF MOSQUES IN THE 4.0 ERA? - Aditya Fadillah Azka; Andien Mirza Pratiwi; Alda Putri Safira; Galluh Muhammad Dhiya Ulhaq; Novita Novita (Politeknik Negeri Semarang, 2022)
This study aims to determine the understanding of the management of the Mosque Prosperity Council (DKM) about good governance that can be carried out in managing mosques so that they can increase the prosperity of the mosque. The variables that explain good governance consist of transparency, accountability, responsibility, independence, and fairness. As for the level of mosque prosperity, it can be seen from the number of worshipers who come to worship at the mosque, the organization of religious activities and social activities as well as services for mosque congregations. The data used in this study are primary data obtained from interviews with the Mosque Prosperity Council (DKM) which then became the basis for research analysis using qualitative descriptive methods. The sample of this study is a mosque located in the area around the author's residence. The results of this study based on interviews explained that the DKM administrators agreed that by implementing good governance in managing the mosque, it could increase the prosperity of the mosque. Good governance makes mosques able to organize more religious activities and social activities for their congregations.